Sudden hoarseness in severe heart failure - Ortner’s syndrome - Gavric, Jelena; Valjarević, Svetlana; Jovanović, Anđelina; Jovanović, Milan B. (Halo 194 Scientific Journal of Emergency Medicine, 2024)
Introduction: All cardiological conditions that can lead to paralysis of the left or right half of the larynx fall under Ortner’s syndrome. Case Presentation: A 57-year-old patient was urgently admitted to the Cardiology Department due to difficulty breathing and clinical suspicion of heart failure. Urgent otolaryngological consultation was sought for a sensation of choking and hoarseness. Fiberoptic nasopharyngolaryngoscopy revealed restricted mobility of his left hemilarynx. Changes indicative of chronic heart failure were observed on the ECG. Computed tomography of the neck and chest with intravenous contrast confirmed cardiomegaly with mediastinal structure displacement. Conclusion: Hoarseness can be an initial sign of a potentially lethal disease. Early recognition and treatment of the underlying cardiovascular condition are crucial for the patient’s recovery. It is essential to emphasize that a dyspneic patient requires not only an otolaryngologist’s examination but also a thorough cardiological assessment.